Women Who Leave “Home”: The Mother and Daughter in Kôge (1964) - JO, Gyoku (eizogaku, 2023)
Kôge, an adaptation based on the novel of the same name by Sawako Ariyoshi, is the longest of Keisuke Kinoshita’s works. The entire film is based on the love-hate bond between Ikuyo, a mother who has never been a parental figure in her life, living only for her own desires, and Tomoko, a daughter who is tormented by her mother and who constantly forgives her despite feeling hatred towards her.This study focused on the relationship between Tomoko and Ikuyo in Kôge, and shed light on the relationship between mother and daughter, a subject which has not garnered much attention in Kinoshita’s works. I first discussed the character of Ikuyo, and pointed out that Kinoshita’s shooting style of tracking shots and continuous use of zooming suggested Ikuyo’s deviation from the “home”. I also discussed the peculiarity of the mother-daughter relationship in Kôge by comparing it with the family images (especially the mother-child relationship) in Kinoshita’s other works. Furthermore, I discussed Kinoshita’s new interpretations of the mother-daughter bond in comparison with the original work.